Designing a writing assistant for the Nheengatu Language - Pinhanez, Claudio; Cordeiro, Raquel; Bento, João Paulo; Nogima, Julio; Santarelli, Enrico (InfoDesign, 2025)
The recent expansion of internet access in Indigenous villages and communities across the Amazon has opened new opportunities for learning, communication, and cultural exchange. While many young people are bilingual, the predominance of Portuguese in digital environments poses risks to bilingual education and to the preservation of Indigenous languages. This paper presents the development of a digital tool designed to support the written use of Indigenous languages – specifically Nheengatu – within online contexts. The goal is to encourage greater use of Nheengatu on the internet by enabling young people to produce digital content in their own language and to strengthen their familiarity with it in everyday digital practices. We describe the design and co-creation process of these tools, developed in collaboration with Indigenous teachers and students through participatory workshops, usability evaluations, and community interviews. The paper discusses the first learnings from this process and outlines ongoing efforts to expand the initiative to other Indigenous languages and educational settings.